THE GOD OF INTIMACY AND ACTION: reconnecting ancient spiritual practices, evangelism and justice - TONY CAMPOLO and MARY ALBERT DARLING (GREAT BRITAIN JOHN WILEY & SONS, INC, 2007)
The God of Intimacy and Action reveals how contemplative spiritual practices can lead to greater intimacy with God and fuel passion for reaching out to others, through spreading the Good News and fostering justice for the poor and oppressed. The authors show why this combination is not only crucial but historical: it is vividly demonstrated in the lives of saints such as St Francis of Assisi, Ignatius of Loyola, and Catherine of Siena. Campolo and Darling explain mystical spirituality and its practices and integrate them with evangelism and justice to illuminate what they call 'holistic Christianity'. They suggest specific ways to nurture and energize one's spirituality and show how to go beyond living a Christian life that merely emphasizes right beliefs and right behaviours.